Применение эквивалентной модели для оценки состояния систем - Верлань, Анатолий Федорович; Положаенко, Сергей Анатолиевич (Kamianets-Podilskyi National Ivan Ohiienko University, 2018)
The current stage of development of technical systems is characterized by a steady increase in their structural complexity, as well as the complexity of their functions. This circumstance leads to the need to improve the technological preparation of production systems, which is associated with the need to ensure strict requirements for testing the latter both at the manufacturing stage and at the operation and maintenance stages.Although there is considerable experience in solving these problems, however, problems of methodological support of the process of diagnosing (and testing) remain, guaranteeing the receipt of specified performance indicators of a fairly wide class of technical systems, which ultimately makes it possible to increase the reliability of estimates of the technical condition of these systems.In some cases, a diagnostic experiment should be performed under conditions when the system being diagnosed cannot be decommissioned or access to its internal elements (subsystems) is difficult (limited). An effective and efficient approach in this case is the use of their models to obtain estimates of the operability of real systems, which allow for the inclusion of the above conditions for conducting a diagnostic experiment. Moreover, theoretical studies of recent years have shown that when solving most of the problems of diagnosis, the model-controlled system pair is underdetermined. From a practical point of view, the solution of the problem of diagnosing using a system model is reduced to an equivalent identification problem, during the solution of which the deviation of the model of the system being diagnosed from a certain standard, which is a model of a serviceable system, is determined.The possibility of using an equivalent system model (in particular, an electrical device) to control its state when the system is not removed from the operating mode is considered. The conditions of equivalence of the model and the real system are determined, as well as the order of choice of parameters by which the state of the system is assessed. The correctness of applying an equivalent model to assess the state of the system without taking the last out of service is shown in a test example.